Persistent deficiency of circulating mucosal-associated invariant T (MAIT) cells in ANCA-associated vasculitis. (June 2016) - Braudeau, Cécile; Amouriaux, Karine; Néel, Antoine; Herbreteau, Guillaume; Salabert, Nina; Rimbert, Marie; Martin, Jérôme C.; Hémont, Caroline; Hamidou, Mohamed; Josien, Régis
Abstract: Objective: Mucosal associated invariant T cells (MAIT) and innate lymphoid cells (ILCs) have immunoregulatory functions at mucosal sites and have been involved in various inflammatory and autoimmune diseases. The aim of this study was to assess their frequencies in blood in ANCA-associated vasculitis (AAV). Methods: The frequencies and function of MAIT cells, ILCs, γδT, iNKT, NK cells were analyzed by flow cytometry on PBMC of patients with granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) without any treatment, in acute (AP) and remission phase (RP) and compared with healthy controls (HC). Results: The frequencies of MAIT cells were strongly decreased in GPA and MPA in AP compared to HC, both in never treated and in relapsing patients and independently of patient age. This was associated with an activated phenotype of patient MAIT cells, as shown by increased expression of CD69 and IFNγ. MAIT cells remained decreased during RP in AAV patients. The frequencies of iNKT and γδT cells were unaffected compared to HC, whereas those of NK cells were slightly reduced during AP in MPA. We also observed a significant decrease in frequencies of total ILCs with decreased ILC2 and ILC3 and increased ILC1 during AP in both GPA and MPA compared to HC. These frequencies normalized during RP. Interestingly, we observed a significant correlation between the frequency of total ILCs and BVAS. Conclusion: We show for the first time that AAV are associated with a major decrease and an activated phenotype of blood MAIT cell. These features persisted during remission suggesting a role for MAIT cells in the pathogenesis of AAV. Highlights: MAIT cells frequencies are strongly reduced in blood of AAV patients. MAIT cells from AAV patients exhibit an activated phenotype and increase IFNg production. MAIT cell frequencies do not normalize during remission.